DRONE STADIUM INTERACTIVE SYSTEM - Petras Zigmantas Barčkus; Vidmantas Rimavičius; Dangis Rimkus; Dalius Makackas (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
The article proposes new access to the use of drones and the development of their technical capabilities. Innovative features include an interactive drone flying track offering cordless sensors. The interactive route, via wireless, is associated with a real-time WEB graphical interface. The result of the project is the Drone stadium interactive system, realised with wireless sensors. According to the selected criteria, requirements are set for the system design. The project aims to create a space without pilots with cordless sensors and link them with a real-time user interface, thus extending the application of the abovementioned stadiums or hangars by improving the technical capabilities of the system or its components.